Women in the Third Reich - Stibbe, Matthew 1969- (Arnold [u.a.], 2003)
"Women in the Third Reich takes a fresh and critical look at the work of recent experts on the social history of the Third Reich and, in particular, highlights the role of women as actors on the historical stage." "Included is a critical discussion of the legacy of the Nazi regime for women and the women's movement in post-1945 Germany." "A variety of previously unavailable primary sources (including party records, newspaper articles and women's testimonies and memories) are used, making Women in the Third Reich essential reading for anyone interested in the social history of Nazi and post-war Germany."--BOOK JACKET